Early childcare arrangements and children's internalizing and externalizing symptoms: an individual participant data meta-analysis of six prospective birth cohorts in EuropeResearch in context - Katharine M. Barry; Demetris Avraam; Tim Cadman; Ahmed Elhakeem; Hanan El Marroun; Pauline W. Jansen; Anne-Mari; Katrine Strandberg-Larsen; Llúcia González Safont; Raquel Soler-Blasco; Florencia Barreto-Zarza; Jordi Julvez; et al. (Elsevier, 2024)
Summary: Background: Early childcare attendance may be related to children's internalizing and externalizing symptoms throughout childhood and young adolescence, however evidence from Europe is limited. We aimed to assess this association across multiple population-based birth cohorts of children recruited in different European countries. Methods: Data come from six parent-offspring prospective birth cohort studies across five European countries within the EU Child Cohort Network. A total of 87,208 parent-child dyads were included in the study. To test associations between childcare attendance (centre-based or informal) anytime between ages 0 and 4 years and children's internalizing and externalizing symptoms in middle childhood and young adolescence (measured at: 5-6 years, 7-9 years, and 10-13 years) a two-stage individual participant data meta-analysis was implemented. Linear regression models were performed in each cohort separately; combined random-effects meta-analysis was then used to obtain overall association estimates. In secondary analyses, we tested interactions between childcare attendance and mother's post-partum depression, low education status, and the child's sex. Findings: Compared to children who were exclusively cared for by their parents prior to school entry, those who attended centre-based childcare had lower levels of internalizing symptoms in all age groups [5-6 years: β: −1.78 (95% CI: −3.39, −0.16); 7-9 years: β: −0.55 (95% CI: −0.88, −0.73); 10-13 years: β: −0.76 (95% CI: −1.15, −0.37)]. Children who attended informal childcare appeared to have elevated levels of internalizing symptoms between 7-9 and 10-13 years, respectively [β: 1.65 (95% CI: 1.25, 2.06); β: 1.25 (95% CI: 0.96, 1.54)]. Informal childcare attendance was also associated with increased levels of children's externalizing symptoms between 7-9 and 10-13 years, respectively [β: 2.84 (95% CI: 1.41, 4.26); β: 2.19 (95% CI: 0.54, 3.84)]. Interpretation: Early centre-based childcare is associated with decreased levels of children's internalizing symptoms compared to exclusive parental care. For informal childcare, opposite associations were observed. Overall, our results suggest that centre-based childcare attendance may be associated with slight positive impacts on children's emotional development and should be encouraged by public policies. In addition, children from socioeconomically disadvantaged families require special attention, as they may not sufficiently benefit from universal early childhood education and care (ECEC). Funding: This research was funded by the ERC Consolidator grant RESEDA (Horizon Europe, 101001420).